Biology of Drug-Induced Gingival Hyperplasia: In Vitro Study of the Effect of Nifedipine on Human Fibroblasts - Dorina Lauritano; Giulia Moreo; Fedora Della Vella; Annalisa Palmieri; Francesco Carinci; Massimo Petruzzi (Applied Sciences, 2021)
Background: It has been proven that the antihypertensive agent nifedipine can cause gingival overgrowth as a side effect. The aim of this study was to analyze the effects of pharmacological treatment with nifedipine on human gingival fibroblasts activity, investigating the possible pathogenetic mechanisms that lead to the onset of gingival enlargement. Methods: The expression profile of 57 genes belonging to the “Extracellular Matrix and Adhesion Molecules” pathway, fibroblasts’ viability at different drug concentrations, and E-cadherin levels in treated fibroblasts were assessed using real-time Polymerase Chain Reaction, PrestoBlue™ cell viability test, and an enzyme-linked immunoassay (ELISA), respectively. Results: Metalloproteinase 24 and 8 (MMP24, MMP8) showed significant upregulation in treated cells with respect to the control group, and cell adhesion gene CDH1 (E-cadherin) levels were recorded as increased in treated fibroblasts using both real-time PCR and ELISA. Downregulation was observed for transmembrane receptors ITGA6 and ITGB4, the basement membrane constituent LAMA1 and LAMB1, and the extracellular matrix protease MMP11, MMP16, and MMP26. Conclusions: The obtained data suggested that the pathogenesis of nifedipine-induced gingival overgrowth is characterized by an excessive accumulation of collagen due to the inhibition of collagen intracellular and extracellular degradation pathways.